Ritualizing Jesus' Grief at Gethsemane1. (December 2018) - Harkins, Angela Kim
New light can be cast on Jesus' grief-stricken prayer by contextualizing it within the growing scholarship on prayers and ritual mourning practices in the Second Temple period. The emotional prayer that Jesus prays in Gethsemane can be understood as a reenactment of a recognizable Second Temple ritual that joined emotional prayers of supplication and confession to mourning practices. This article proposes that a Second Temple ritual context is an overlooked but potentially fruitful way of understanding the ancient controversies that embroiled Jesus' prayer at Gethsemane. The cultural specificity of the emotions associated with this prayer can help to account for why ancient Greek and Roman readers experienced such sharp and divergent responses to Jesus' prayer.